Abnormal vulval lesions: diagnosis and management - Kothari, Aarti; Parekh, Usha; Mahajan, Rashmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Vulval symptoms are commonly found and cause considerable distress for women. Symptoms are often chronic and can significantly affect the quality of women's lives including sexual function and wellbeing. Despite the frequency of vulval symptoms, women often find it difficult to seek medical advice due to multiple reasons, mostly cultural and emotional. This part is not easily self-observable neither are women aware of the fact that a vulvar lesion could also be a manifestation of a systemic disease. The idea behind this study was to identify whether presenting vulval lesion is dermatological or non-dermatological and to control the symptoms, to identify nature of the various vulvar lesions (inflammatory or neoplastic) and to identify those skin lesions not responding to treatment which require biopsy and further management. It was a clinical descriptive study. Cases included women with vulvar lesions who attended Gynaec OPD at Dhiraj General Hospital affiliated to S.B.K.S. Medical Institute and Research Centre of Vadodara. After taking their informed consent ,all the women who had symptoms like vaginal discharge, itching or discomfort associated a with vulvar lesion, visible lesion or growth over vulva were thoroughly investigated to rule out any systemic illness causing vulvar lesion following which biopsy was taken if solid growth or a non-healing lesion was present. Treatment was done according to the lesions. In the presence of vulvar complains, a diagnostic pathway including systematic physical examination is always mandatory to detect SCC early. A non-healing lesion must be subjected to biopsy mandatorily. Women should be educated to avoid ODC drugs or creams when they face vulval lesions.